The δ13C, δ18O and Δ47 records in biogenic, pedogenic and geogenic carbonate types from paleosol-loess sequence and their paleoenvironmental meaning. (May 2021) - Zamanian, Kazem; Lechler, Alex R.; Schauer, Andrew J.; Kuzyakov, Yakov; Huntington, Katharine W.
Abstract: Paleoenvironmental reconstructions are commonly based on isotopic signatures of a variety of carbonate types, including rhizoliths and land-snail shells, present in paleosol-loess sequences. However, various carbonate types are formed through distinct biotic and abiotic processes over various periods, and therefore may record diverging environmental information in the same sedimentological layer. Here, we investigate the effects of carbonate type on δ 13 C, δ 18 O, and clumped isotope-derived paleotemperature [T(Δ47 )] from the Quaternary Nussloch paleosol-loess sequence (Rhine Valley, SW Germany). δ 13 C, δ 18 O, and T(Δ47 ) values of co-occurring rhizoliths (-8.2‰ to -5.8‰, -6.1‰ to -5.9‰, 12–32°C, respectively), loess dolls (-7.0‰, -5.6‰, 23°C), land-snail shells (-8.1‰ to -3.2‰, -4.0‰ to -2.2‰, 12–38°C), earthworm biospheroliths (-11‰, -4.7‰, 8°C), and "bulk" carbonates (-1.9‰ to -0.5‰, -5.6‰ to -5.3‰, 78–120°C) from three sediment layers depend systematically on the carbonate type, admixture from geogenic carbonate, and the duration of formation periods. Based on these findings, we provide a comprehensive summary for the application of the three isotopic proxies of δ 13 C, δ 18 O, and Δ47 in biogenic and pedogenic carbonates present in the same sediment layer to reconstruct paleoenvironments (e.g., local vegetation, evaporative conditions, and temperature). We conclude that bulk carbonates in Nussloch loess should be excluded from paleoenvironmental reconstructions. Instead, pedogenic and biogenic carbonates should be used to provide context for interpreting the isotopic signature for detailed site- and time-specific paleoenvironmental information.